Calponin-3 is critical for coordinated contractility of actin stress fibers - Ciuba, Katarzyna; Engel, Ulrike (Scientific reports, 2018)
Contractile actomyosin bundles, stress fibers, contribute to morphogenesis, migration, and mechanosensing of non-muscle cells. In addition to actin and non-muscle myosin II (NMII), stress fibers contain a large array of proteins that control their assembly, turnover, and contractility. Calponin-3 (Cnn3) is an actin-binding protein that associates with stress fibers. However, whether Cnn3 promotes stress fiber assembly, or serves as either a positive or negative regulator of their contractility has remained obscure. Here, we applied U2OS osteosarcoma cells as a model system to study the function of Cnn3. We show that Cnn3 localizes to both NMII-containing contractile ventral stress fibers and transverse arcs, as well as to non-contractile dorsal stress fibers that do not contain NMII. Fluorescence-recovery-after-photobleaching experiments revealed that Cnn3 is a dynamic component of stress fibers. Importantly, CRISPR/Cas9 knockout and RNAi knockdown studies demonstrated that Cnn3 is not essential for stress fiber assembly. However, Cnn3 depletion resulted in increased and uncoordinated contractility of stress fibers that often led to breakage of individual actomyosin bundles within the stress fiber network. Collectively these results provide evidence that Cnn3 is dispensable for the assembly of actomyosin bundles, but that it is required for controlling proper contractility of the stress fiber network.
Gesehen am 21.05.2019